2012
DOI: 10.1002/wsb.100
|View full text |Cite
|
Sign up to set email alerts
|

Canopy characteristics affect reproductive success of golden‐cheeked warblers

Abstract: The golden‐cheeked warbler (Setophaga chrysoparia), listed by the U.S. Fish and Wildlife Service as endangered in 1990 due primarily to habitat loss and fragmentation, is a Neotropical migrant songbird that breeds exclusively in mature juniper–oak (Juniperus–Quercus) woodlands in central Texas, USA. Previous studies suggested suitable breeding habitat consists of >35% canopy closure (with 50–70% cover optimal), and ≥10% oak composition. However, little is known about this species' habitat relationships at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Thus, our results provide some new insight into understanding how to describe where vireos occur and may help guide future investigations into why vireos occur where they do. For both species, recent research has suggested that previously assumed habitat relationships may in fact vary across the species' ranges, among years, among individuals, and in the context of various social and behavioral conditions (Pope 2011, Klassen et al 2012, Smith et al 2012. The capacity to estimate vegetation height and perhaps other structural metrics remotely to relate to species response variables among years, across regions, and even among territories or nest sites can provide an essential tool for developing a more complete and accurate understanding of the habitat associations for these species and provide insight into the mechanisms driving these patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our results provide some new insight into understanding how to describe where vireos occur and may help guide future investigations into why vireos occur where they do. For both species, recent research has suggested that previously assumed habitat relationships may in fact vary across the species' ranges, among years, among individuals, and in the context of various social and behavioral conditions (Pope 2011, Klassen et al 2012, Smith et al 2012. The capacity to estimate vegetation height and perhaps other structural metrics remotely to relate to species response variables among years, across regions, and even among territories or nest sites can provide an essential tool for developing a more complete and accurate understanding of the habitat associations for these species and provide insight into the mechanisms driving these patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We erred on the side of being inclusive in the sampling frame, not a priori restricting sampling to areas generally considered habitat for either species (Wilkins et al 2005, Groce et al 2010) because recent research indicates habitat use may differ from previous assumptions (Pope 2011, Klassen et al 2012, Smith et al 2012). We generated a 300 3 300 m grid of sample points initiated at a random starting point (n ¼ 1341; Thompson 2002).…”
Section: Sample Survey Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat Variables.-Habitat features associated with nest-site selection can affect avian nest survival by influencing predation rates, nest defense, microclimates, and food abundance for provisioning young (e.g., Newlon and Saab 2011, Klassen et al 2012, Kozma and Kroll 2012. We sampled habitat characteristics related to the nest cavity, nest tree, and surrounding vegetation that were thought to influence survival of Red-headed Woodpeckers' nests.…”
Section: Studymentioning
confidence: 99%
“…Thus, a new PVA is warranted and might significantly alter our outlook on GCWA viability. In recent years much effort has been expended to update our knowledge on GCWA abundance and reproduction both at the local and range-wide scale (e.g., abundance, Hunt et al 2012, Collier et al 2013, Peak and Thompson 2013, Warren et al 2013reproduction, Campomizzi et al 2012, Klassen et al 2012, Marshall et al 2013. Apparent survival (Φ) has been estimated for juvenile (hatch year, HY) and adult (after hatch year, AHY) male GCWAs while accounting for imperfect detection in the past, where Φ is the probability that an individual remains alive and returns to the study area from one sampling occasion to the next.…”
Section: Introductionmentioning
confidence: 99%